Analyzing the relationship between dietary factors and anemia to improve preventive behavior in adolescent girls in Denpasar - Wibawa, Anak Agung Ngurah Alit Dwi Nanda; Weta, I Wayan; Ani, Luh Seri; Awan, Syuma Adhy (Science Midwifery, 2025)
Adolescents are at risk of developing anemia related to an unbalanced diet, habits of consuming low-iron foods, and substances that inhibit iron absorption, such as tea or coffee. Based on this, this study is aimed at finding out the relationship between diet and anemia status in adolescent girls. A cross-sectional study was conducted on 91 female students who were selected by the proportional random sample method. The research was conducted at SMAN 4 Denpasar-Bali, Indonesia. Hemoglobin level data was measured using a hemoglobinometer. Anemia is defined by a hemoglobin level of less than 12 g/dL. Diet and nutrient intake data were collected by questionnaire method using a quantitative food frequency questionnaire. The data were analyzed univariate and bivariate. The Mann-Whitney U test was carried out to determine factors related to anemia in adolescent girls. The results of the study found that the proportion of anemia in adolescent girls was 38.5%. Vitamin C intake was found to be related to anemia (p value <0.05). Meanwhile, protein intake, iron, fiber, frequency of meals and menstrual blood loss score (KDM) were found not to be related to anemia status (p>0.05). It can be concluded that a diet high in vitamin C is associated with anemia in adolescent girls. The results of this study contribute to the prevention of anemia through dietary improvements in adolescent girls, so it is recommended for adolescent girls to maintain a balanced diet to meet nutritional needs, including the need for iron.